A neo-Schumpeterian perspective on the analytical macroeconomic framework: The expanded reproduction system - Bogang Jun; Tai-Yoo Kim (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
This study aims to introduce a new analytical macroeconomic framework, the expanded reproduction system, that combines the accumulated wisdom of several contemporary economic models while also compensating for their shortcomings. This new framework may be used to study macroeconomic phenomena from both the supply and demand side over a number of different time intervals. Furthermore, as we account for both new product and productivity innovations, we are able to account for both qualitative and quantitative developments within the economy.
urn:nbn:de:bsz:100-opus-11545
Keywords: 330; Schumpeterian Economics; New Classical Synthesis; Macroeconomics; Economic Policy